KOLABORASI KEPEMIMPINAN ADAT DAN PEMERINTAHAN DALAM PENGAMBILAN KEPUTUSAN PADA PROGRAM TPS-3R DI SANUR, BALI - Setiawati, Ni Putu Ari (Jurnal Ilmiah Cakrawarti, 2023)
This research aims to analyze the strategies and roles of public sector leadership in managing government collaboration, focusing on a case study in Sanur, Bali. In the context of the increasing number of residents and tourists, waste management through 3R waste processing sites (reduce, reuse, and recycle) becomes crucial. The research method used is qualitative, with data collection through interviews, observations, and documentation studies. The research results show that effective leadership and collaboration between traditional leaders and local government play an important role in increasing community participation and the success of waste management programs. However, there are significant challenges, such as the lack of human resources and financial support that can hinder policy implementation. This research is expected to provide recommendations for policymakers to strengthen collaboration between the public sector and the community to achieve sustainable environmental management goals.